A Jewish philosopher of Baghdad: 'Izz al-Dawla Ibn Kammūna (d. 683/1284) and his writings - Pūrǧawādī, Riḍā (Islamic philosophy, theology, and science 0169-8729, 2006)
Ch. 1 Introduction 1 Survey of previous scholarship 1 2 Notes on Ibn Kammuna's biography 8 3 Ibn Kammuna's philosophical thought 23 4 The reception of Ibn Kammuna in later Muslim thought 28 5 The reception of Ibn Kammuna in Judaism 54 Ch. 2 Inventory of the writings of Ibn Kammuna 1 Authentic writings 59 2 Works of uncertain authenticity 128 Ch. 3 Editions of selected writings of Ibn Kammuna Text 1 Kalimat wajiza mushtamila 'ala nukat latifa fi l-'ilm wa-l-'amal 139 Text 2 Ithbat al-mabda' wa-sifatihi wa-l-'amal al-muqarrib ila llah 186 Text 3 Taqrib al-mahajja wa-tahdhib al-hujja 196 Text 4 Min ta'aliq al-Hakim 'Izz al-Dawla Abi 1-Rida Ibn Kammuna 207 Text 5 Correspondence with Nasir al-Din al-Tusi 209 Text 6 Correspondence with Najm al-Din al-Katibi 211 Text 7 Correspondence with Kamal al-Din al-Bahrani 221 Text 8 Correspondence with Fakhr al-Din al-Kashi 222 Text 9 Ibn Kammuna's poetry 224 App. A The Firkovitch/Shapira Codex of Ibn Kammuna's Sharh al-Talwihat 225 App. B Kitab fi ithbat al-nubuwwa li-Muhammad 'alayhi al-salam